2023
DOI: 10.3390/diagnostics13020213
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of the Biceps Muscle in Idiopathic Parkinson’s Disease with Deep Brain Stimulation: Rigidity Can Be Quantified by Shear Wave Elastography

Abstract: Rigidity in Parkinson’s disease (PD) is assessed by clinical scales, mostly the Unified Parkinson’s Disease Rating Scale of the Movement Disorders Society (MDS-UPDRS). While the MDS-UPDRS-III ranges on an integer from 0 to 4, we investigated whether muscle ultrasound shear wave elastography (SWE) offers a refined assessment. Ten PD patients (five treated with deep brain stimulation (DBS) and levodopa, five with levodopa only) and ten healthy controls were included. Over a period of 80 min, both the SWE value a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For example, in Movie 3, the estimated SoS can be associated with the state of the biceps muscle as it transitions from one state to another. Recently, it has been shown that ultrasound of the biceps using shear wave elastography can help assess rigidity in Parkinson's disease [43]; SoS estimation, like elastography, quantitatively measures a biomechanical property of the muscle tissue. Our work can aid in the clinical translation work for relating tissue SoS with muscle health and function.…”
Section: B Importance Of Live Speed-of-sound Estimation Frameworkmentioning
confidence: 99%
“…For example, in Movie 3, the estimated SoS can be associated with the state of the biceps muscle as it transitions from one state to another. Recently, it has been shown that ultrasound of the biceps using shear wave elastography can help assess rigidity in Parkinson's disease [43]; SoS estimation, like elastography, quantitatively measures a biomechanical property of the muscle tissue. Our work can aid in the clinical translation work for relating tissue SoS with muscle health and function.…”
Section: B Importance Of Live Speed-of-sound Estimation Frameworkmentioning
confidence: 99%
“…In vivo characterization of skeletal muscles is crucial for understanding musculoskeletal diseases and improving treatment strategies. For this, the non-invasive ultrasound shear wave elastography (SWE) has recently been shown to represent both passive [1] , [2] , [3] , [4] and active muscle mechanics [5] , [6] , [7] , [8] in healthy cohorts and several studies have demonstrated the clinical potential for SWE, for example for patients diagnosed with myotonia [9] , Duchenne muscular dystrophy [10] , myasthenia gravis [11] or Parkinson [12] . However, applying SWE on skeletal muscles poses challenges due to the muscles' complex and heterogeneous architecture.…”
Section: Introductionmentioning
confidence: 99%